2021
DOI: 10.1002/cb.1920
|View full text |Cite
|
Sign up to set email alerts
|

Examining corporate social responsibility awareness: An unaided recall measure

Abstract: As professional sports teams commonly partner with multiple charity organizations to achieve corporate social responsibility objectives, the purpose of this research was to measure charity brand awareness among sports fans via unaided recall. Further, this study proposed antecedents to awareness, including; level of fandom, overall season‐ticket holder (STH) satisfaction, perceptions of on‐field performance, live game viewership frequency, televised game viewership frequency, and digital channel interaction fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…However, existing research on CSR has not demonstrated the specific transmission mechanism of its spillover effects. For example, some studies generally have a clear target audience, such as ECSR for consumers and ICSR for employees (Hameed et al, 2016; Liu & Xu, 2023; Rayne et al, 2021), but have not yet explored the impact of corporate fulfillment of ICSR on consumers, non‐direct stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…However, existing research on CSR has not demonstrated the specific transmission mechanism of its spillover effects. For example, some studies generally have a clear target audience, such as ECSR for consumers and ICSR for employees (Hameed et al, 2016; Liu & Xu, 2023; Rayne et al, 2021), but have not yet explored the impact of corporate fulfillment of ICSR on consumers, non‐direct stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…There is a notion that businesses hoping to achieve customer loyalty see it as a crucial part of their organization's objectives (Oliver, 1999). Numerous researchers consider attitudinal loyalty (ATTL) as a precursor of behavioral loyalty (BHL) (Bandyopadhyay & Martell, 2007;Carpenter, 2008;Rayne, 2019). On the other hand, some scholars contradict the assertion that ATTL is the antecedent of BHL.…”
Section: Introductionmentioning
confidence: 99%